2020
DOI: 10.1590/0034-7167-2018-0943
|View full text |Cite
|
Sign up to set email alerts
|

Professional skills for health promotion in caring for tuberculosis patients

Abstract: Objectives: to understand the health promotion skills found in the speeches of health practitioners in care for TB patients. Methods: qualitative study, developed with seven practitioners involved in care for TB patients, identified from a sociocentric approach, whose speeches were submitted to analysis based on the health promotion skills model in the Galway Consensus. Results: there were four domains: Catalyzing change; Leadership; Planning; and Partnerships. These domains resulted from health education ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 19 publications
0
7
0
7
Order By: Relevance
“…The competence domain "Catalyzing changes" capacitates individuals and communities to improve health by fostering the production of changes through the empowerment and autonomy of the subjects, being a health practice's instrument of transformation (14) . Of the evidenced findings, this competence is contemplated by nurses when they encourage and stimulate women from their community in this competence through educational practices and conversation circles on women's health issues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The competence domain "Catalyzing changes" capacitates individuals and communities to improve health by fostering the production of changes through the empowerment and autonomy of the subjects, being a health practice's instrument of transformation (14) . Of the evidenced findings, this competence is contemplated by nurses when they encourage and stimulate women from their community in this competence through educational practices and conversation circles on women's health issues.…”
Section: Discussionmentioning
confidence: 99%
“…Health educational actions can empower women to construct new knowledge and knowing, which will revert in preventive or health promotion actions (14) . Empowerment is one of the pillars Chart 2 -Nurses' competence domains regarding the promotion of women's health according to the Galway Consensus, Brejo Santo, Ceará, Brazil, 2018…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the difficulty about the lack of health education reported by the study participants. It was observed in another investigation that the development of health promotion actions through educational actions promotes catalytic changes which are evidenced by the strengthening, participation and protagonism of individuals and the community in the management of self-care 31 .…”
Section: Discussionmentioning
confidence: 99%
“…The nurse received a prominent role, when considered as the professional that parents turn to in the first place to clarify doubts, thus showing their humanized attention and focus on solving problems in the process of making decisions, and the bond of trust [ 19 ]. Indeed, several studies reported that trust is an element associated with high levels of parental satisfaction, the well-being of the child and parents, acceptance and adherence to treatment, and parental involvement in decision-making regarding children’s treatment [ 20 ].…”
Section: Discussionmentioning
confidence: 99%